Identifikasi, Penanganan, dan Penyelesaian Kredit Bermasalah pada Bank Perkreditan Rakyat - Epriliyana, Nike Norma; Salsabila, Arin Puri; Tohari, Nursyamsida (ACCOUNT (Journal of Accounting and Finance), 2024)
Rural Banks is a financial institution that focuses on providing funds and providing credit. In the distribution of credit, Rural Banks can experience payment bottlenecks because debtors do not have sufficient funds, experience bankruptcy, do not pay on time. Bad credit can cause disruption to the liquidity of the Rural Bank. This research aims to explain the factors that cause bad credit and solutions to handling bad credit at Rural Banks. The research approach was carried out with a qualitative descriptive approach with a review of articles on non-performing loans. Data collection is done by literature study.. The results of the study concluded that the factors that cause non-performing loans include: (1) Improper credit analysis; (2) Less selective credit policy; (3) The debtor is not honest about the reported income; (4) The debtor has a disaster; (5) The weak financial strength of the business owned by the debtor. Based on these influencing factors, the solutions for handling non-performing loans include: (1) Early warning; (2) Credit restructuring; (3) Settlement of non-performing loans.